COLOR DATA CLUSTERING ALGORITHMS (CDCA) USING SPATIAL TEMPORAL DATA MINING (Global Journal of Advanced Engineering Technologies and Sciences, 2015)
The clustering algorithm in coloring basis is describes in two different ways. The first section discusses about different color object, here to cluster same color of objects only which is specified in the runtime. The algorithm is specifying all necessary steps are followed to cluster colouring objects. The second section deals with the maximum wind details are Hurricane/Tropical Data for Northern Indian Ocean from the website of http://weather.unisys.com/hurricane/. Here to concentrate the flow record of maximum wind, starting from the year 2001 to 2013, the maximum cyclone flow updated in different duration i.e., hourly basis. The databases keep all records of data, to apply the clustering for coloring based. The wind color is different for the range basis. The database store all the wind ranges and to generate the coloring range, the SQL query to retrieve in the prescribed range format.